Tff1-expressing Tregs in lung prevent exacerbation of Bleomycin-induced pulmonary fibrosis - Okamoto, Masaaki; Kuratani, Ayumi; Okuzaki, Daisuke; Kamiyama, Naganori; Kobayashi, Takashi; Sasai, Miwa; Yamamoto, Masahiro (Frontiers in Immunology, 2024)
Bleomycin (BLM) induces lung injury, leading to inflammation and pulmonary fibrosis. Regulatory T cells (Tregs) maintain self-tolerance and control host immune responses. However, little is known about their involvement in the pathology of pulmonary fibrosis. Here we show that a unique Treg subset expressing trefoil factor family 1 (Tff1) emerges in the BLM-injured lung. These Tff1expressing Tregs (Tff1-Tregs) were induced by IL-33. Moreover, although Tff1 ablation in Tregs did not change the pathological condition, selective ablation of Tff1-Tregs using an intersectional genetic method promoted pro-inflammatory features of macrophages in the injured lung and exacerbated the fibrosis. Taken together, our study revealed the presence of a unique Treg subset expressing Tff1 in BLM-injured lungs and their critical role in the injured lung to ameliorate fibrosis.